The Mesoaccumbens Pathway: A Retrograde Labeling and Single-Cell Axon Tracing Analysis in the Mouse - Rodríguez-López, Claudia; Clascá, Francisco; Prensa, Lucía (Frontiers in Neuroanatomy, 2017)
Neurons in the ventral tegmental area (VTA) that innervate the nucleus accumbens (Acb) constitute the so-called mesoaccumbens system. Increased activity by these neurons is correlated with the expectation and achievement of reward. The mesoaccumbens projection neurons are regarded as a central node in the brain networks that regulate drive and hedonic experience, and their dysregulation is a common pathophysiological step in addictive behaviors as well as major depression. Despite previous anatomical studies that have analyzed the origin of the mesoaccumbens axons within the VTA, regarded as a unit, the exact contributions of the various cytoarchitectural subdivisions of the VTA to this innervation is still unexplored; understanding these contributions would help further our understanding of their precise anatomical organization. With the aim of deciphering the contribution of the various VTA subdivisions to accumbal innervation, the present study has used retrograde tracer microinjections in the Acb to map the location within the various VTA subdivisions of neurons targeting either the shell or core compartments of the Acb in mice. Furthermore, the dopaminergic nature of these projections has also been analyzed using tyrosine-hydroxylase immunohistochemistry. We demonstrate here that small territories of the Acb core and shell are innervated simultaneously by many VTA subdivisions, contributing dopaminergic as well as non-dopaminergic axons to the accumbal innervation. In fact, single VTA subdivisions harbor both dopaminergic and non-dopaminergic neurons that project to the same accumbal territory. The most medial VTA subnuclei, like the caudal linear nucleus, project abundantly to medial aspects of the Acb core, whereas more lateral territories of the Acb are preferentially targeted by neurons located in the parabrachial pigmented and paranigral nuclei. Overall, about half of the mesoaccumbens neurons are putatively dopaminergic in mice. Anterograde single-cell labeling (Sindbis-pal-eGFP vector) of a limited sample of neurons revealed that mesoaccumbens neurons form profuse terminal arborizations to cover large volumes of either the Acb core or shell, and, unlike other VTA projection neuron populations, they do not branch to other striatal or extrastriatal structures. These anatomical observations are consistent with reports of an intense response in many Acb neurons after stimulation of very few VTA cells.